2021
DOI: 10.1002/slct.202101898
|View full text |Cite
|
Sign up to set email alerts
|

Comparative MD Study of Inhibitory Activity of Opaganib and Adamantane‐Isothiourea Derivatives toward COVID‐19 Main Protease Mpro

Abstract: In this study, the inhibitory potency of four adamantlyisothiourea derivatives (compounds 1 [4-bromobenzyl (Z)-N'-(adamantan-1-yl)-4-phenylpiperazine-1-carbothioimidate], 2 [3,5-bis(trifluoromethyl)benzyl (Z)-N'-(adamantan-1-yl)-4-phenylpiperazine-1-carbothioimidate], 3 [4-bromobenzyl (Z)-N-(adamantan-1-yl)morpholine-4-carbothioimidate] and 4 [3,5-bis (trifluoromethyl)benzyl (Z)-N-(adamantan-1-yl)morpholine-4carbothioimidate]) was evaluated against SARS-CoV-2 targeted proteins. The investigated compounds 1-4 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Jovanović et al [143] 85 HsEH, RsEH, MsEH (IC 50 0.4 nM each) Chloro group on adamantane moiety enhanced the activity.…”
Section: Kadernani Et Al Have Reported the Synthesis Of Variousmentioning
confidence: 95%
See 1 more Smart Citation
“…Jovanović et al [143] 85 HsEH, RsEH, MsEH (IC 50 0.4 nM each) Chloro group on adamantane moiety enhanced the activity.…”
Section: Kadernani Et Al Have Reported the Synthesis Of Variousmentioning
confidence: 95%
“…Jovanović et al have synthesized a novel class of adamantane hybrids containing isothiourea moiety and screened for their inhibitory activity against coronavirus disease 2019 (COVID‐19) main protease Mpro using a molecular docking technique. [ 143 ] Hybrid 84 displayed better potency than the reference opaganib. Codony et al have reported the synthesis of benzohomoadamantane hybrids and assessed in vivo inhibitory activities against human, rat, and murine sEH.…”
Section: Pharmacological Activities Of Adamantane‐based Hybridsmentioning
confidence: 99%
“… 19,20 Recently, Marković and his co-workers studied, adamantane-isothiourea derivatives have strong inhibition potency towards Mpro and mutation of SARS-CoV-2 Spike protein D614G. 21 Coumarin derivatives and their Pd( ii ) complexes have stronger binding affinity with Mpro of SARS-CoV-2 compared to the FDA approved drugs. 22 These studies explored that natural compounds and their derivatives potent inhibitors for Mpro of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%